Clinical efficacy of laparoscopic radical hepatectomy and laparotomy for hepatocellular carcinoma and factors of postoperative recurrence - Cao, Qing; Yang, Liang; Zhou, Guanbao; Hu, Yue (Frontiers in Oncology, 2023)
Objective: For exploring the clinical efficacy of laparoscopic radical hepatectomy and laparotomy for liver cancer and analysing related factors of postoperative recurrence. Methods: Totally 212 patients with liver cancer admitted to our hospital between April 2017 and December 2020 were enrolled, and all of them were followed up after operation. According to the treatment modes, the patients were assigned to a laparotomy group (n=106) and a laparoscopic group (n=106). Perioperative indicators, hematological examination results, complications and recurrence were compared between the two groups. The recurrence time of liver cancer after operation was confirmed by imaging examination with definite mass, and multivariate analysis was used for analyzing the risk factors associated with postoperative recurrence Results: The laparoscopic group experienced longer operation time and shorter incision length, less intraoperative blood loss, early time to have the first off-bed activity and time to eat liquid and shorter hospital stay than the laparotomy group (all P<0.05). Seven days after operation, the laparoscopic group showed notably lower levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TBIL), tumour necrosis factor-α (TNF-α), interleukin-8 (IL-8), and C-reactive protein (CRP) than the laparotomy group (all P<0.05), and also showed notably higher levels of immunoglobulin A (IgA), IgG and IgM than the laparotomy group (all P<0.05). Additionally, the laparotomy group showed a higher lower total incidence rate of complications than the laparoscopic group (19.81% vs. 9.43%, P<0.05). During the one-year follow-up, the laparotomy group was not greatly different than the laparoscopic group in recurrence rate (22.64% (24/106) vs. 16.98% (18/106), P>0.05). Multivariate analysis showed that average tumour diameter and microvascular invasion were risk factors for postoperative recurrence (P<0.05). Conclusion: Laparoscopic radical hepatectomy for liver cancer can reduce the influence on liver function and immune function, with less damage to tissues, and can ameliorate postoperative inflammatory reaction, and promote postoperative recovery of patients as soon as possible, bringing benefits to the prognosis of patients. There are many factors influencing postoperative recurrence of liver cancer, and average tumour diameter and microvascular invasion are the risk factors.